Feature Extraction Method for Planar Four-bar Mechanism with Design Requirement of Finitely Separated Position - Ding Jiansheng; Liu Wenrui; Sun Jianwei (Jixie chuandong)
Aiming at the problem that the numerical atlas method can’t be used to synthesize the finitely separated positions design requirements for the planar four-bar mechanism,based on the complex function least square method,a method for realizing the feature extraction of finitely separated positions discrete points is proposed by using the Fourier series approximation fitting finitely separated position. The relationship of feature parameters between the finitely separated positions and their transformations,including translation,rotation,and scaling is found. Combining with numerical atlas method,the finitely separated positions design requirements path generation of the planar four-bar mechanism is realized. Examples are presented to illustrate the applicability and effectiveness of the proposed method.